A case of spontaneous gastric perforation in a 3 years old male child - Dhar, Pinak Pani; Dey, Abhik (International Surgery Journal, 2022)
A 3 years old boy attended emergency department with history of abdominal distension, fever, vomiting, loose stools for 5 days. The boy was suffering from epilepsy from last 1 year of age and was under treatment. From history and clinical examination, it seemed to be a case of peritonitis. Abdominal ultrasound revealed debrigenous free fluid in peritoneal cavity. Emergency exploratory laparotomy done and pyloric perforation was noted and repaired by modified graham’s patch. The child, post-operatively, suffered from dys-electrolytemia and wound site infection and recovered with treatment.